Effects of aneuploidy on gene expression: implications for cancer. (8th December 2015) - Dürrbaum, Milena; Storchová, Zuzana
Abstract : Unbalanced chromosome content, so‐called aneuploidy, is a hallmark of cancer cells. Changes in the copy numbers of chromosomes or large chromosomal regions significantly alter the expression of several hundreds of genes that are gained or lost. At the same time, aneuploidy per se affects the transcription of many genes throughout the entire genome, as several pathways are activated or inhibited in response to changes in chromosome copy number. In recent years, a large amount of quantitative genome, transcriptome and proteome data has enabled comparison of the changes in gene expression observed in aneuploid cancer cells, as well as in model aneuploid cells with defined karyotypes. Here, we summarize how aneuploidy shapes gene expression and how it may contribute to the phenotypes of cancer cells. Abstract : Aneuploidy, defined as unbalanced changes in chromosome number, results in altered expression of genes that are gained or lost. Besides these direct consequences on gene expression, aneuploidy also affects gene expression genome‐wide, a phenomenon manifested in the transcriptional activation or downregulation of multiple pathways. But do these changes also contribute to the phenotypes of aneuploid cancer cells?